Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 38. Beitrag. Coleoptera: Catopidae (exclusive Bathysciinae). - Szymczakowski, Waclaw (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The present paper gives a comparative survey of the Catopidae (except the cavernicolous subfamily Bathysciinae) from the Balkan countries and a list of the species found in Albania up to now. The greater part of the material had been collected by A. Bischoff in 1934 and 1936. 19 species were examined, 10 of which were new in the fauna of Albania. There are now 21 species of Catopidaenon Bathysciinae known from that country.